Kampanye Komunikasi Kesehatan dalam Perecepatan Penanganan di Kabupaten Kota (Studi Kasus:Bidang Kesehatan Biro Kesejahteraan Rakyat Provinsi Jawa Barat) - Hamidah, Hamidah; Sophia, Evi (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2024)
This study health communication related to stunting prevention in the Districts and Cities of West Java Province, where the prevalence of stunting reaches around 20.2%, approaching the WHO target of below 20%. Qualitative research methods were used to explore the efforts of the People's Welfare Bureau in reducing stunting rates. The findings show that the People's Welfare Bureau of West Java Province shows a strong commitment with positive support from districts and cities, as well as effective coordination between provincial and regional governments. The strategic approach through educational campaigns aims to increase awareness of balanced nutrition and child health care. This campaign utilizes mass media, social media, and community activities to expand the reach of information, motivate the community, and encourage active participation. Overall, the health communication campaign plays a crucial role in changing community behavior and preventing stunting sustainably.